A study evaluating third trimester haemoglobin level as a predictor of feto-maternal outcome in pregnancy induced hypertension cases - Das, Sasmita; Pattanaik, Tapan; Sahu, Manisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of this study is to assess whether third trimester haemoglobin level can be used as a predictor of feto-maternal adverse outcomes in pregnancies complicated with PIH. Methods: This is an observational study in the Obstetrics and Gynaecology Department of IMS and SUM hospital, SOA university from July 2015 to December 2017. Institutional ethical committee permission obtained. All singleton pregnancies delivered during this period with PIH were included in the study. PIH and eclampsia was diagnosed as per ISSHP criteria. All chronic hypertension cases excluded. All were evaluated with haemoglobin level. They were divided into 3 groups depending upon haemoglobin level; low (<11gm%), normal (11-13gm%) and high haemoglobin group (> 13gm%) considering the WHO standard. Maternal complications observed were incidence of eclampsia, abruptio placentae, HELLP syndrome, PPH, neurological complications, ICU admissions and death. Fetal outcomes studied were NICU admission, stillbirth, incidence of prematurity and low birth weight. All these parameters were compared among 3 groups. Statistical analysis was done with SPSS 20 software using Yate’s corrected chi square test. Results: Incidence of eclampsia was significantly greater with both high (p<0.001) and low (p=0.0085) haemoglobin level than normal haemoglobin level. Maternal complications and adverse perinatal outcomes (stillbirth, low birth weight, prematurity, NICU admission) are significantly greater with high haemoglobin level than cases with normal haemoglobin level. There is no significant difference in maternal and perinatal complications between low and normal haemoglobin group. Conclusions: High haemoglobin level >13gm% in third trimester is associated with worst feto-maternal outcome whereas normal haemoglobin level (11-13gm%) is associated with least feto-maternal complications.